Rethinking Javanese Sufism: From Ascetic Protest to Institutional Power - Said, Imam Ghazali; Maram, Ahmad Nabilul; Muhdi, Muhdi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
This article re-examines Javanese Sufism through the lenses of hierarchy, determinism, and free will, adding an explicit economic-political dimension often absent from earlier studies. Drawing on participant observations in three pesantren, semi-structured interviews, and textual analysis of classical and Javanese scholarship, the analysis showed how charismatic teachers and guides converted spiritual authority into material patronage networks, while disciples negotiated between Jabarī rhetoric and pragmatic agency. Two ideal types emerged: an ascetic current that framed free will as self-discipline and distance from power and a common, devotional current that sacralized the submission of the self through collective dhikr and pilgrimage economies. These two approaches can explain Sufism’s success in spreading Islam in Java and its current traction among economically marginal groups. By linking doctrinal debate with money flow, the study extends current scholarship on religion and social change and provides a framework for assessing governance and accountability in Sufi institutions. Sufi institutions are advised to adopt transparent budget disclosure and participatory decision-making so that charismatic authority is balanced by measurable good governance safeguards.